Cataloging practices of four theological and seminary school libraries a survey - Manglal-lan, Christine M.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This research focuses on the cataloging practices of four theological and seminary school libraries belonging to the Asia Graduate School of Theology (AGST), with the purpose of determining the strengths and weaknesses in the cataloging and classification activities of the four libraries under study. The study seeks to: 1) identify the people doing the cataloging work; 2) determine their qualifications and whether they are engaged in tasks other than cataloging; 3) identify the practices and policies involved in the cataloging and classification of library materials; and 4) find out if computers are used in cataloging. The descriptive research method used: questionnaires and informal interviews.
The findings reveal that: 1) cataloging and classification are done by the chief librarians themselves; 2) three of the four libraries have personnel holding BLS and/or MLS degrees and are engaged in other tasks; 3) all libraries follow the rules/codes in the AACR2; 4) three of the four libraries maintain a divided public catalog; 5) published codes of filing rules are followed by them; 6) the four libraries measure their cataloging outputs by counting the number of titles and/or bound volumes cataloged/recataloged and/or classifies/reclassified; 7) the four libraries utilize the LCC; 8) all of the libraries use notations, the Cutter-Sanborn numbers/letters and initial letters of authors; 9) all of them use the LCSH; 10) all libraries use the BIB-BASE software; 11) and the catalogers catalog 20 to 30 titles a day.
This study recommends the following: (1) the administration should employ a more reasonable number of qualified and trained personnel so that cataloging work can be finished in less time; (2) the librarians should come up with a plan of employing one full-time librarian to coordinate the shared cataloging activities; (3) the librarians should devise a common thesaurus in theology; (4) the catalogers should consult teachers and translators to assist them whenever they are cataloging books written in different languages; (5) the librarians should work together to establish a database for the use of the group; (6) a common type of public catalog should be maintained by all of them; and (7) the ABS library is recommended as the center for the envisioned centralized cataloging.
Computer print out (photocopy).
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Cataloging -- Philippines -- Quezon City; Seminary scchool libraries -- Philippines -- Quezon City; Theological libraries -- Philippines -- Quezon City